Reconstruction of a Holocene landslide-dammed lake in the Yalong basin, eastern Tibetan Plateau - Wang, Hao; Yang, Anna; Jiang, Shengfan; Liu, Nannan (Frontiers in Earth Science, 2023)
Abstract: The failures of natural dams formed by landslides and glaciers in mountain areas have triggered the most destructive flood events on Earth. It has been shown that outburst floods are effective agents in modifying landscapes, such as curving bedrock gorges and transporting surface masses. Reconstructing the ages and magnitudes of prehistoric landslide damming events allows us to capture the full range of frequencies and magnitudes of similar events and deepen our understanding of the interaction between large landslides and trunk rivers in tectonically active high-relief mountains. Previous studies have revealed many paleo-landslide-dammed lakes in the Yarlung Tsangpo River and its tributaries, the Jinsha River and Min River. However, most studies associated with paleo-event reconstruction usually lack an estimation of the extent and volume of paleo-landslide-dammed lakes. Actually, the paleo-level of a landslide-dammed lake can be recorded in the variation in the sedimentary sequence and the geometry of the breach channel of a landslide dam, which have not been fully exploited. In this study, we identified a series of sedimentary evidence formed by an ancient landslide-dammed lake in the Liqiu River, a left-bank tributary of the Yalong River. Based on sedimentary analysis, we inferred that the minimal lake volume of this ancient lake was approximately 2.4 × 108 m3, corresponding to a lake level at 3187 m a.s.l. The maximal lake extent derived from relict dam morphology reveals a lake volume of 3.2 × 108 m3 at the level of 3200 m a.s.l. An initial drainage occurred as the lake water overtopped the landslide dam, which was suggested to explain the small discrepancy in the lake level. The relict lake has remained stable over a long period of time and has accommodated continuous clay varve deposits. Furthermore, the OSL dating results illustrate that the dammed lake initiated before 7.9 ka BP and persisted until at least 3.9 ka BP. The long-term cumulative coupled effect of tectonic movement and the rapid river incision rate provided favourable conditions for the failure of the Yuting landslide.